The Importance of Primary Historical Sources in Local History Research - Zukhrufa Ken Satya Dien; Hilma Rosdiana (Medan Resource Center, 2026)
This study examines the significance of primary historical sources in conducting local history research, focusing on identifying their types and evaluating their role in the reconstruction of local historical narratives. The research addresses how primary sources contribute to the credibility and depth of historical inquiry. A qualitative approach is employed using a literature study method to analyze both written and unwritten sources within the framework of historical methodology. The findings indicate that local history research relies heavily on the availability and proper utilization of primary sources, which are broadly categorized into written and unwritten forms. The study also reveals that the use of such sources requires rigorous verification processes, including source criticism, to ensure authenticity, reliability, and analytical depth. The argument advanced in this study emphasizes that the quality of local historiography is determined not merely by the quantity of sources, but by the critical evaluation and contextual interpretation applied by historians.